Pemanfaatan dan Bioaktivitas Jatropha gossypiifolia L. - Marina Silalahi (Pro-Life, 2023)
Jatropha gossypiifolia (Euphorbiaceae) is a plant introduced in Indonesia, and its use as traditional medicine has not been widely used. This study aims to explain the botany, utilization, bioactivity and toxicity of J. gossypiifolia. The research method was carried out using library research, especially articles that can be accessed online using the keywords J. gossypiifolia, uses J. gossypiifolia and bioactivity of J. gossypiifolia. Morphologically, J. gossypiifolia is easily recognized from its young red leaves which produce white latex and red flowers. The J. gossypiifolia is a medicinal plant that is widely used in various countries, especially throughout Africa and America. In traditional traditional medicine such as overcoming vomiting), promoting blood flow, overcoming itching, blood purifier, antibacterial, anti-fertile, anticancer, antiulcer, and stomach ache. The bioactivity as an anti-microbial, anti-oxidant, anti-inflammatory anti-fertility and hepatoprotective analgesic, of J. gossypiifolia is anticoagulant, anti-hypertensive, anti-Alzheimer’s, and anti-diabetes mellitus. The extract of J. gossypiifolia is capable of growing Plasmodium berghei which causes malarial fever, which has better activity than quinine. Therefore, it is very potential to be developed as an alternative in the treatment of malaria, therefore it needs to be studied further. The latex produced from the stems and leaves of J. gossypiifolia is toxic and therefore needs to be used with caution. Keywords: J. gossypiifolia, anti-malarial, anti-microbial